(NpORTRETY PIANISTOWs (NmONOGRAFIQs - (NcYPIN(B. (Ngs ((NmOSKWAs (NkOMPOZITORs, 1982)
(Nw KNIGE POME]ENA SERIQ PORTRETOW(B,(NPOSWQ]ENNYH SOWETSKIM MASTERAM FORTEPIANNOGO ISPOLNITELXSKOGO ISKUSSTWA(B.s
Keywords: (NMONOGRAFIQs